Studi Analisis Penanganan Anak Putus Sekolah Di Desa Ngepanrejo Kecamatan Bandongan Kabupaten Magelang - Muamalah, Bad'ul, Dra Ratnasari Diah Utami, M.Si, M.Pd (2017)
Essay, The Faculty of Teacher Training and Education,Muhammadiyah University of Surakarta. February, 2017. This study aims to: 1) Describe the causes of school dropouts in the village Ngepanrejo. 2) Describe the impact the children out of school in the village Ngepanrejo. 3) Describe how the solution for the handling of dropouts. The research is a qualitative research with case study design. The informants are Lurah, Kadus, parents drop out of school, school dropouts and homeroom. Data collection techniques used were observation, interviews, and documentation. The validity of research data using a triangulation of sources and methods. The results showed that:1). The cause of school dropouts there are two things: the internal factors are: the child and the pain in the suffering, external factors include: environmental, economic and social factors.2). dropouts as well as multiply the impact of unemployment, a burden to the village, and a lack of insight. 3). Efforts to tackle school dropouts among others: to join Packet, holding lectures, and provide skills for children out of school in order to have the provision for later life